Review of Vasileios Petrogiannis, European Mobility and Spatial Belongings: Greek and Latvian Migrants in Sweden - Petri, Rolf (Historein, 2022)
Review of Vasileios Petrogiannis, European Mobility and Spatial Belongings: Greek and Latvian Migrants in Sweden. Stockholm: Elanders, 2020. 334 pp. <a title="Open access" href="https://ejournals.epublishing.ekt.gr/index.php/historein/copyeditor/viewMetadata/Vasileios%20Petrogiannis%20European%20Mobility%20and%20Spatial%20Belongings:%20Greek%20and%20Latvian%20Migrants%20in%20Sweden%20%20Stockholm:%20Elanders,%202020.%20334%20pp.%20http:/urn.kb.se/resolve?urn=urn:nbn:se:sh:diva-41915" target="_blank" rel="noopener">http://urn.kb.se/resolve?urn=urn:nbn:se:sh:diva-41915 To view the full text, click on the button "HTML".